Comparing high-performing education systems: understanding Singapore, Shanghai, and Hong Kong. Issue 1 (2nd January 2022) - La Londe, Priya Goel; Verger, Antoni
ABSTRACT: Despite the trendsetting of East Asian HPES, education policy commentary and literature on this region remains rather underdeveloped and predictable. In Comparing High-Performing Education Systems: Understanding Singapore, Shanghai, and Hong Kong, Dr Charlene Tan moves scholarship on East Asian HPES in a new, sorely needed direction. This review essay of Comparing High-Performing Education Systems describes the guiding conceptual framework of the book and summarizes the book, chapter-by-chapter. This review essay also comments on two striking issues – the explanatory power of Confucian habitus, and the intersectionality of performativity, Confucianism, and neoliberalism. The aim in this review essay is to both celebrate the boldness of Comparing High Performing Systems and offer questions to further enrich the employment of Confucianism as a conceptual and analytical tool to examine education policies, processes, and outcomes in East Asian systems.